An algorithm of parameter identification in applied crop ontogenesis models - Denisovas, Vitalijus; Juščenko, Natalija (Lietuvos matematikos rinkinys, 2005)
The objective of the paper is to discuss the development and adaptation to selected region soil and climate conditions of applied grain crop development models considering possibilities of their incorporation to integrated information modelling system DIASPORA. The proposed parameter identification algorithm of applied crop development model was approved using standard meteorological and agrometeorological data obtained from Lithuanian Hidrometeorological Service and Lithuanian Institute of Agriculture.